Sarcoidosis with cryptococcal infection apparently engaging only immune-privileged body compartments: a case report - Johannes H. van der Stoep; Eva Sigstad; Anders Bredberg (BMC Infectious Diseases, 2020)
Abstract Background Infection with the Cryptococcus neoformans yeast fungus is largely restricted to patients with HIV, sarcoidosis or immunosuppressive therapies. In sarcoidosis, there is intense local immune response in granuloma lesions, coupled with a paradoxical systemic anergy. An analysis of cryptococcal infection in sarcoidosis may therefore shed light on whether opportunistic pathogens preferentially engage immune-privileged tissues. Case presentation A 54-year-old man was admitted to our hospital after 2 months with palpitations and activity-related presyncope. A chest X-ray was normal, electrocardiography showed type-II atrioventricular-block, and there was a tentative diagnosis of myocarditis. Computed tomography reported minor hilar lymph glands and multiple nodular lesions in the lungs. Magnetic resonance imaging showed oedema and nodular structures in the heart, and fibrosis and granulomas were found in endomyocardial biopsies. The diagnosis was revised to cardiac sarcoidosis, and prednisone was initiated. In parallel, positron-emission tomography had revealed a marked uptake in the right thyroid lobe, a thyroid lobectomy was then performed, and the pathology showed a BRAF-positive papillary thyroid carcinoma. Four days postoperatively the patient developed symptoms suggestive of meningoencephalitis. Cerebrospinal fluid and blood cultures yielded growth of C. neoformans. Fungal staining of the thyroid specimen revealed cryptococcal elements in the carcinoma and in granulomas close to the tumour. Notably, there was no evidence of cryptococci in the heart sarcoid sections or in the normal thyroid parenchyma. The patient was successfully treated with antifungal agents and at the 2-year follow-up there was no evidence of thyroid cancer relapse. Conclusion This sarcoidosis patient had a remarkable clinic with evidence of cryptococcal infection only in body compartments commonly regarded to be immune-privileged. The findings suggest that an opportunistic and environmentally abundant pathogen, when infecting an immunocompromised host, primarily engages immunodeficient locations such as the brain, a tumour microenvironment and some forms of granuloma.